Pengaruh Konseling Kelompok Pendekatan Behavioristik Terhadap Penyesuaian Diri Siswa - Nurbaina Siagian (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2020)
This study aims to determine the effect of behavioristic approach group counseling services on the adjustment of class VIII-4 students of MTs Negeri 2 Medan. This type of research is Quasi experimental design with Pre test-post test one group design. The population in this study were students of class VIII-4 MTs Negeri 2 Medan T.A. 2019/2020, amounting to 35 people. The sample in this study were 8 students of class VIII-4 with low levels of self-adjustment. The instrument used was a self-adjustment scale of 51 items with a total reliability of 0.465. From the calculation results, the pre-test score in the experimental group obtained an average of = 140 while the post-test data obtained an average of = 171. The data were analyzed using the Wilcoxon test to see whether there was a significant effect of group counseling with a behavioristic approach in increasing student adjustment. From the results of the Wilcoxon test shows that the Wilcoxon level test obtained Jcount = 16 while Jtabel = 4.From the table the critical value J for the Wilcoxon cascade test for n = 8, α = 0.05 in accordance with the criteria for acceptance and rejection of the hypothesis, the hypothesis is accepted if Jhitung> Jtabel, namely Jhitung> Jtabel where 16> 4, from this calculation it can be seen that the treatment in the experimental group means that the hypothesis that says there is a significant effect of group counseling with a behavioristic approach on the adjustment of class VIII-4 students of MTs Negeri 2 Medan is acceptable